The role of the complement system in primary membranous nephropathy: A narrative review in the era of new therapeutic targets - So, Benjamin Y. F.; Chan, Gary C. W.; Yap, Desmond Y. H.; Chan, Tak Mao (Frontiers in Immunology, 2022)
Primary membranous nephropathy (MN) is an important cause of nephrotic syndrome and chronic kidney disease (CKD) in the adult population. Although the discovery of different autoantibodies against glomerular/podocytic antigens have highlighted the role of B cells in the pathogenesis of MN, suboptimal response or even resistance to B cell-directed therapies occurs, suggesting that other pathophysiological mechanisms are involved in mediating podocyte injury. The complement system plays an important role in the innate immune response to infection, and dysregulation of the complement system has been observed in various kidney diseases. There is compelling evidence of complement cascade activation in primary MN, with the mannose-binding lectin (MBL) and alternative pathways particularly implicated. With appropriate validation, assays of complements and associated activation products could hold promise as adjunctive tools for non-invasive disease monitoring and prognostication. While there is growing interest to target the complement system in MN, there is concern regarding the risk of infection due to encapsulated organisms and high treatment costs, highlighting the need for clinical trials to identify patients most likely to benefit from complement-directed therapies.